Pemberdayaan Masyarakat Melalui Pembuatan Produk Teh Gaharu di Desa Wisata Koto Sentajo Kabupaten Kuantan Singingi - Yasir Yasir; Yohannes Firzal; Chelsy Yesicha; Andri Sulistyani; Safri Safri (Unri Conference Series: Community Engagement, 2021)
Koto Sentajo Village is a traditional village that maintains traditions so that it has a tourist attraction. This village has a lot of potential, but still has problems to be an independent village. In this case, this service activity aims to provide the ability to manage agarwood plants to improve the community's economy as the village's superior product. This service activity is targeted at BUMDes managers, farmer groups and PKK women. This service method uses a Community Based Tourism (CBT) approach. The implementation of service activities is carried out by starting with community socio-economic mapping, holding FGDs, and providing training. Service activities found that there was a lot of potential on the one hand, but on the other hand there were still problems with the community's economy. The FGD was held to discuss the problems that exist in Koto Sentajo Village. This FGD activity contributes to increasing community understanding of the importance of developing gaharu plants, because this village has a large forest area and land as a provider of raw materials. The training focused on the manufacture, packaging and marketing of gaharu tea as the village's flagship product. This training has a positive impact on the community, however, it is still constrained by licensing issues to be developed in a larger and wider production scale.